Intergenerational Flows of Time and Goods: Consequences of Slowing Population Growth - Lee, Ronald D.; Lapkoff, Shelley (Journal of Political Economy, 1988)
It is feared that low fertility and older age distributions in the developed countries might cause lower life cycle consumption because of the increased pension and health cost burden. The theoretical literature on intergenerational transfers has addressed this question but has considered only the consumption of market goods and has made no serious empirical attempt to measure the theoretical concepts necessary to assess the problem. This paper develops a theoretical model of intergenerational transfers incorporating time use. With the aid of time budget and consumer expenditure surveys, empirical estimates of the age profiles of various types of time and goods consumption are presented, and we conclude that (1) the net direction of intergenerational transfers is from younger to older ages; (2) under the golden-rule assumption, these transfers largely constitute an externality to childbearing; and (3) they are not large enough to offset the capital dilution effect that would result from higher fertility and more rapid population growth.